2016
DOI: 10.1038/srep37172
|View full text |Cite
|
Sign up to set email alerts
|

ELMO1 protects renal structure and ultrafiltration in kidney development and under diabetic conditions

Abstract: Engulfment and cell motility 1 (ELMO1) functions as a guanine exchange factor for Rac1 and was recently found to protect endothelial cells from apoptosis. Genome wide association studies suggest that polymorphisms within human elmo1 act as a potential contributing factor for the development of diabetic nephropathy. Yet, the function of ELMO1 with respect to the glomerulus and how this protein contributes to renal pathology was unknown. Thus, this study aimed to identify the role played by ELMO1 in renal develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…They confirmed the animal data with immunohistochemical analysis of human kidneys from patients with DKD. Those authors concluded that the overexpression of the ELMO1 gene occurs due to the glomerular protection and survival of renal cells by decreasing apoptosis under hyperglycaemic conditions [19].…”
Section: Snp Genotypingmentioning
confidence: 99%
“…They confirmed the animal data with immunohistochemical analysis of human kidneys from patients with DKD. Those authors concluded that the overexpression of the ELMO1 gene occurs due to the glomerular protection and survival of renal cells by decreasing apoptosis under hyperglycaemic conditions [19].…”
Section: Snp Genotypingmentioning
confidence: 99%
“…ELMO1 also serves as a regulator of cyclooxygenase-2 (COX-2) activity, which aggravates glomerular injury and thus stimulates COX-2-mediated fibronectin accumulation in the development of glomerulosclerosis [51]. However, Sharma et al [52] found that ELMO1 exerts a protective effect on the kidneys in zebrafish and human samples. Their results highlighted ELMO1 as an important factor for glomerular protection and renal cell survival by decreasing apoptosis, especially under diabetic conditions.…”
Section: Inflammation and Oxidative Stress-related Genesmentioning
confidence: 99%
“…NCAM2 is primarily expressed in the brain, where it stimulates neurite outgrowth and facilitates dendritic and axonal compartmentalization [23]. ELMO1 protects endothelial cells from apoptosis [24] and it is also an important factor for glomerular protection and renal cell survival via decreasing apoptosis, especially under diabetic conditions [25].…”
Section: Discussionmentioning
confidence: 99%